Pemanfaatan Aset Daerah (Studi tentang pola kemitraan asset tanah Pemerintah Provinsi Jawa Timur) - Sugeng Riyono (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2013)
The study ofÂ partnership in public administration are perspectives of regional autonomy, the new public management and governance theory, the theory of partnerships, institutional theory, management theory of public goods, and asset management theories. Research recommendation, that in order to utilize Â land assets as much as 831 fields, needs to be done: 1) Changes in regional policy (policy reform), the manager of three bureaus into one agency (agency) alone, 2) strategies and strengthening institutional partnerships as an effort to utility the management of regional assets ; 3) Management of regional assets (public goods) by utilizing the technology of administration (asset inventory, budget cycle and e-procurement) in increasing local revenue (funding incomes).Keywords : Â regional asset, asset management, land asset utility, and partnerships.